How do you solve #1/(3m)+(6m-9)/(3m)=(3m-3)/(4m)#?

1 Answer
Nov 27, 2016

Answer:

#m=0 " "Or" "m=23/15#

Explanation:

#1/(3m)+(6m-9)/(3m) = (3m-3)/(4m)#
#" "#
#rArr(1+6m-9)/(3m)=(3m-3)/(4m)#
#" "#
#" "#
#rArr(-8+6m)/(3m)=(3m-3)/(4m)#
#" "#
#" "#
#rArrcolor(blue)((-8+6m)xx4m = (3m-3)xx3m)#
#" "#
#" "#
#rArr-32m + 24m^2 = 9m^2-9m#
#" "#
#" "#
#rArr-32m + 24m^2 - 9m^2+9m=0#
#" "#
#" "#
#rArr15m^2-23m=0#
#" "#
#" "#
#rArrm(15m-23)=0#
#" "#
#m=0#
# " "#
Or
#" "#
#15m - 23 =0rArr15m = 23rArrm=23/15#